2022
DOI: 10.3390/cells11142259
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Multidrug-Resistance (MDR) Transporters in Developing Human Fetal Brain Endothelial Cells

Abstract: There is little information about the functional expression of the multidrug resistance (MDR) transporters P-glycoprotein (P-gp, encoded by ABCB1) and breast cancer resistance protein (BCRP/ABCG2) in the developing blood–brain barrier (BBB). We isolated and cultured primary human fetal brain endothelial cells (hfBECs) from early and mid-gestation brains and assessed P-gp/ABCB1 and BCRP/ABCG2 expression and function, as well as tube formation capability. Immunolocalization of the von Willebrand factor (marker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The angiogenesis of fetal BMECs in humans may be related to P-gp (Barakat et al, 2008 ). In vitro studies on human primary fetal BMECs detected P-gp in capillary-like microvessels, cytoplasm, and cell nuclei through immunolocalization (Lye et al, 2022 ). Tsai et al ( 2002 ) showed that in the mouse brain, P-gp expression is lower both during late embryogenesis and early neonatal period and increases gradually during brain maturation (P21), where P-gp protein levels approached adult levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The angiogenesis of fetal BMECs in humans may be related to P-gp (Barakat et al, 2008 ). In vitro studies on human primary fetal BMECs detected P-gp in capillary-like microvessels, cytoplasm, and cell nuclei through immunolocalization (Lye et al, 2022 ). Tsai et al ( 2002 ) showed that in the mouse brain, P-gp expression is lower both during late embryogenesis and early neonatal period and increases gradually during brain maturation (P21), where P-gp protein levels approached adult levels.…”
Section: Resultsmentioning
confidence: 99%
“…Tsai et al ( 2002 ) showed that in the mouse brain, P-gp expression is lower both during late embryogenesis and early neonatal period and increases gradually during brain maturation (P21), where P-gp protein levels approached adult levels. Nevertheless, even though P-gp protein and ABCB1 gene expression are lower during early and mid-gestational periods, its function does not change, and it works enough to protect BBB (Lye et al, 2022 ). The lower expression seems to be conserved since it was observed in mice, rats, and humans (Schinkel et al, 1994 , 1995 ; Matsuoka et al, 1999 ; Watchko et al, 2001 ; Tsai et al, 2002 ; Daood et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional expression of P-gp and BCRP has been demonstrated in isolated human fetal brain endothelial cells (hfBECs) derived from early and mid-gestation [ 9 ]. These results indicate that P-gp and BCRP at the BBB protect the developing CNS from early-gestation and throughout mid-pregnancy.…”
Section: Introductionmentioning
confidence: 99%